PENGARUH AIPengaruh Air Rebusan terhadap Kualitas Ikan Kembung Rebus (Rastrelliger sp.)aR REBUSAN TERHADAP KUALITAS IKAN GEMBUNG REBUS (Rastrelliger sp) - M.Yusri Dadan Nugraha; Riyanto riyanto; Hanifah Mutia Z.N Amrul (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2019)
The research on bacterial testing on boiled water of boiled mackerel (Rastelliger sp) has been conducted. The study applied treatment of boiled water that is not replaced and is used continuously in several stages. This study aims to determine the effect of boiled water on the quality of fish production, and determine its effect on meat tectrus, gill color, and aromas. The study was conducted with a descriptive qualitative method. Boiled mackerel quality is measured using the total plate count method, which is to count the number of bacterial colonies in the water before boiling and after boiling.